DC Characteristics Optimization of a Double G-Shield 50 V RF LDMOS - Xiangming Xu; Pengliang Ci; Xiaoyu Tang; Jing Shi; Zhengliang Zhou; Jingfeng Huang; Peng-Fei Wang; David Wei Zhang (Advances in Condensed Matter Physics)
An N-type 50 V RF LDMOS with a RESURF (reduced surface field) structure of dual field plates (grounded shield, or G-shield) was investigated. The effect of the two field plates and N-drift region, including the junction depth and dopant concentration, on the DC characteristics was analyzed by employing the Taurus TCAD device simulator. A high BV (breakdown voltage) can be achieved while keeping a low RDSON (on-resistance). The simulation results show that the N-drift region dopant concentration has an obvious effect on the BV and RDSON and the junction depth affected these values less. There is an optimized length for the second field plate for a given dopant concentration of the N-drift region. Both factors should be optimized together to determine the best DC characteristics. Meanwhile, the effect of the first field plate on the BV and RDSON can be ignored. According to the simulation results, 50 V RF LDMOS with an optimized RESURF structure of a double G-shield was fabricated using 0.35 µm technologies. The measurement data show the same trend as the TCAD simulation, where a BV of 118 V and RDSON of 26 ohm·mm were achieved.